Regulations in services sectors and their impact on downstream industries The OECD 2013 Regimpact Indicator - Égert, Balázs (OECD Economics Department Working Papers, 2016)
This document presents the new 2013 set of the OECD Regulatory Impact (REGIMPACT) indicator. It measures the impact of regulatory barriers to competition in non-manufacturing sectors on all industries, through intermediate inputs. The paper describes how the indicator is calculated and discusses a number of challenges and trade-offs when constructing the indicator. They relate to the composition of the indicator, how the slow-moving or time-invariant retail and professional services regulation data are integrated with the annual energy, transport and communication regulation (ETCR) indicator and what sector weights are used for the calculation of the REGIMPACT indicator. The document then compares the 2003, 2008 and 2013 vintages of the REGIMPACT indicator and the alternative (narrow and wide) definitions of the 2013 indicator. Finally, the paper uses sectoral data to illustrate the extent to which different vintages and alternative indicator definitions can possibly influence sector-level panel regression results for outcome variables such as productivity, investment and labour inputs